Study Of The Mass Construction Of Al Irsyad Mosque In The Kota Baru Parahyangan - Andiyan Andiyan; Firmansyah Firmansyah (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Al Irsyad Mosque is situated in Bandung, Indonesia, in Kota Baru Parahyangan, Padalarang. The construction of this mosque started on September 7, 2009, and was completed a year later. This mosque is modeled after the Kaaba in Makkah's Grand Mosque. This mosque was named one of the five finest buildings in the world in 2010 by the National Frame Building Association in the area of